Short and long-range cyclic patterns in flows of DNA solutions in microfluidic obstacle arrays. Issue 7 (20th February 2023) - Ström, Oskar E.; Beech, Jason P.; Tegenfeldt, Jonas O.
Abstract : A physical viscoelastic phenomenon with strong relevance for processing of ultrahigh concentrations of biomolecules is described, specifically macroscopic waves in high-concentration DNA solutions in micropillar arrays. Abstract : We observe regular patterns emerging across multiple length scales with high-concentration DNA solutions in microfluidic pillar arrays at low Reynolds numbers and high Deborah numbers. Interacting vortices between pillars lead to long-range order in the form of large travelling waves consisting of DNA at high concentration and extension. Waves are formed in quadratic arrays of pillars, while randomizing the position of the pillar in each unit cell of a quadratic array leads to suppression of the long-range patterns. We find that concentrations exceeding the overlap concentration of the DNA enables the waves, and exploring the behavior of the waves as a function of flow rate, buffer composition, concentration and molecular length, we identify elastic effects as central to the origin of the waves. Our work may not only help increase the low throughput that often limits sample processing in microfluidics, it may also provide a platform for further studies of the underlying viscoelastic mechanisms.